2011
DOI: 10.1002/bmc.1671
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics as a novel diagnostic approach for gastrointestinal cancer

Abstract: Conventional tumor markers are unsuitable for detecting carcinoma at an early stage and lack clinical efficacy and utility. In this study, we attempted to investigate the differences in serum metabolite profiles of gastrointestinal cancers and healthy volunteers using a metabolomic approach and searched for sensitive and specific metabolomic biomarker candidates. Human serum samples were obtained esophageal (n = 15), gastric (n = 11), and colorectal (n = 12) cancer patients and healthy volunteers (n = 12). A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 30 publications
3
107
1
Order By: Relevance
“…22). However, other studies by Zhang and colleagues (23) and Ikeda and colleagues (24) showed no significant difference in serum tyrosine levels in patients with esophageal and gastric cancer compared with controls.…”
Section: Tyrosinementioning
confidence: 88%
See 1 more Smart Citation
“…22). However, other studies by Zhang and colleagues (23) and Ikeda and colleagues (24) showed no significant difference in serum tyrosine levels in patients with esophageal and gastric cancer compared with controls.…”
Section: Tyrosinementioning
confidence: 88%
“…Miyagi and colleagues (20) also showed significantly decreased plasma tryptophan concentrations in gastric cancer cases compared with controls (P < 0.01). However, Ikeda and colleagues (24) found no significant difference in tryptophan between patients with esophageal or gastric cancer when compared with healthy controls.…”
Section: Tryptophanmentioning
confidence: 93%
“…We have showed the use of metabolomics for diagnosing and evaluating the pathologic conditions of various diseases (19)(20)(21)(22)(23)(24). Metabolomics is the comprehensive study of low molecular weight metabolites, which are the endpoint of the omics cascade and hence are the closest point in the cascade to the phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these amino acids may be of interest as candidate markers, since the results obtained following the 5-FU and CDDP-treatments support the findings of previous studies. [31][32][33] However, further research is warranted to confirm the selection of amino acids and to evaluate their relationships with different anticancer mechanisms of action.…”
Section: Use Of Loading Plots Of Pca and Pls Analyses To Identify Marmentioning
confidence: 99%